First Detection of Major Viruses Causing Mixed Infections in Melon (Cucumis melo L.) in Bengkulu Province, Indonesia - Mimi Sutrawati; Hendri Bustamam; Sempurna Br. Ginting; Ratna Nabila Pradita; Ella Mustika; Ewa Aulia (Plant Protection Department, Faculty of Agriculture, Universitas Andalas, 2025)
Melon cultivation has increased rapidly in recent years and is frequently associated with widespread virus-like symptoms in Bengkulu Province, Indonesia; however, thereis no formal documentation of the mixed viral infections has been available. Therefore, this study aimed to detect major viruses infecting melon crops in Bengkulu Province and to evaluate their occurrence based on field symptoms and serological detection. Field surveys were conducted at three melon cultivation sites: Kandang Limun Village (Bengkulu City), Air Sebakul Village (Central Bengkulu Regency), and Tawang Rejo Village (Seluma Regency). Symptomatic leaf samples were collected purposively. Virus detection was performed using the Dot Immunobinding Assay (DIBA) with antisera specific to Cucumber mosaic virus (CMV), Tobacco mosaic virus (TMV), and Papaya ringspot virus (PRSV). The results showed that the dominant symptoms of viral infection in melon plants included mosaic, vein banding, chlorosis, leaf curling, and stunted growth in both Snow & Rock and Merlin F1 varieties. Disease incidence varied among varieties and locations, with the highest incidence recorded in Snow & Rock (73.3%). Serological detection revealed that 100% of symptomatic samples tested positive for CMV, TMV, and PRSV, confirming that all infections occurred as mixed infections. This study represents the first report of mixed viral infections in melon crops in Bengkulu Province. These findings demonstrate that overlapping and variable field symptoms cannot be attributed to a single virus and cannot be reliably distinguished through visual diagnosis alone, highlighting the importance of laboratory-based diagnostic approaches for accurate virus identification.